PERAN LEMBAGA TERHADAP PRESTASI OLAHRAGA BULUTANGKIS PADA PELATIHAN BULUTANGKIS ANGKASA di PEKANBARU - Eko Rahmat Saputra; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The problem in this study is about role of institutions on the performance of badminton at Angkasa Badminton Club Pekanbaru. Angkasa Badminton Club is the largest badminton club in Sumatra has been stand for five years. Angkasa Badminton Club has create some good athlete. Angkasa Badminton club has won in regional and national level badminton championship. It is about how the institutions make badminton athlete to reach the achievement. We know all of institutions has different advantage to achieve their own goal. The institutions must give something to make an athlete become a champion, example give the athlete free equipment or scholarship. This is the way to make athlete become more spirit to reach the achievement. All of parents in Angkasa Badminton Club Pekanbaru don’t know about scholarship in there. They only know the club give discount for the equipment that sell in Angkasa Club Pekanbaru. Not only the institutions but all of people in there has responsibility for achievement. Athlete parents must work together with the institutions to reach the achievement. Good institutions must have their own structure organization and rule to achieve the goal. So in this case that we know the institutions has effect to reach the achievementKeywords: Institutions, achievement, scholarship